Ecologization of the Origin of the Ownership Right on the Objects of Fauna in the Aquaculture Area - Getman, Anatoliy; Shehovtsov, Volodymyr (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
The authors of the article have studied theoretical and practical problems of delimitation of the ownership right to the objects of aquaculture and the fauna objects in the context of determining the grounds for the emergence of property right. The mechanisms of resolving disputes concerning the belonging of the fauna objects that are located in a water object together with the objects of aquaculture have been offered. The authors have developed propositions for making amendments and alterations to the current legislation.